Using the Image Media-Based Student Team Achievement Division Model to Improve Learning Outcomes for Elementary School Students - Acoci Acoci; Irman Matje; Krisnawati Krisnawati (AIQU: Journal Multidiscipliner of Science, 2023)
This research aims to improve student learning outcomes in the Social Sciences subject, Sub-theme Cultural Diversity of My Nation through the Student Team Achivemenet Division Learning Model with Image Media for Class IV of Lamangga 1 State Elementary School. The design and model used in this research is the Kemmis and Taggart model which includes planning, implementation, observation, reflection and re-planning and the type of research carried out by the researcher is classroom action research (PTK). From the results of the first cycle evaluation, data was obtained from 22 students, there were 13 students who obtained a KKM score of 65 or classically reaching 59% and 9 students who did not complete 41% with an average score of 65.52 and a weighted score achieved of 1,443. Meanwhile, in cycle II, classically, student learning outcomes increased, where of the 22 students, there were 20 students who obtained a KKM score of 65 or classically reaching 91% and 2 students who did not meet the KKM 9% with an average score of 85.22 and weighted score. achieved was 1,875. Based on the research results, it is concluded that the application of the student team achievement team learning model can improve student learning outcomes in Social Sciences subjects in class IV of Lamangga 1 State Elementary School.